Comet assay for assessment of DNA damage in greenhouse workers exposed to pesticides. (18th August 2019) - Cayir, Akin; Coskun, Mahmut; Coskun, Munevver; Cobanoglu, Hayal
Abstract: Purpose: The main goal of the present study was to determine DNA damage in pesticide-exposed greenhouse workers and pesticides non-exposed controls. Materials and methods: The DNA damage was measured by alkaline comet assay method (pH > 13) in 41 greenhouse workers and 45 non-exposed individuals as the control. Pesticide exposure was assessed by duration of working in the greenhouse and pesticide application in the greenhouse time. DNA damage was estimated by arbitrary unit and damage frequency. Results: Arbitrary unit and damage frequency were consistently significantly higher in greenhouse workers than those of the controls ( p = 0.001). In terms of gender in greenhouse, DNA damage of female workers was significantly higher than those in male workers ( p < 0.05). We found significant correlation between DNA damage and working hours spent. Multiple linear regression analysis showed that working hours in the greenhouse as an indication of pesticide exposure were significantly associated with the DNA damage, which can be attributed to the genotoxic potential of the pesticide mixture. Conclusions: The comet assay is sensitive to detect the damage exposed to chronic effect of pesticides in greenhouse workers. Significant DNA damage was obtained for the exposed group, which was associated with the pesticide exposure.